Robust and thermo-response graphene–PNIPAm hybrid hydrogels reinforced by hectorite clay - Zhang, Enzhong; Wang, Tao; Lian, Cuixia; Sun, Weixiang; Liu, Xinxing; Tong, Zhen (Carbon (New York), 2013)
Graphene oxide (GO) based hydrogels were proposed to be used as biomaterials and stimuli-response materials, but their poor mechanical properties restricted their applications. We enhanced GO–poly(N-isopropylacrylamide) (PNIPAm) hydrogels by hybrid with the hectorite clay through in situ polymerization for the first time. This clay was found to stabilize the GO in the aqueous suspension when a reducer was added in a redox initiating pair. These GO–clay–PNIPAm hybrid hydrogels exhibited a high mechanical strength and extensibility with the GO sheets as the cross-linker and with the hectorite clay as both the cross-linker and reinforcing agent. They were thermal-responsive with the volume phase transition at ∼34°C. Reduction of the GO with l-ascorbic acid under environmental friendly conditions resulted in a high conductivity to the graphene–clay–PNIPAm hydrogels. These graphene–clay–PNIPAm hydrogels still had desirable mechanical properties. This finding has provided an easy method to prepare strong and stimuli-response graphene–polymer hydrogels to meet the demand for the newly developed soft matter.